Effect of prophylactic doses of enoxaparin on antifactor Xa activity confirmed by rotational thromboelastometry in critically ill patients: a preliminary prospective cohort study - Piotr F. Czempik; Piotr F. Czempik; Artur Beberok (Frontiers in Pharmacology)
IntroductionCritically ill patients present multiple risk factors for venous thromboembolism (VTE). Underdosing of antithrombotic medications can result in VTE even as bleeding remains a significant concern for critically ill patients. On the other hand bleeding, remaining a significant concern for the critically ill, can be worsend by overdosing of antithrombotic medications. The present study aimed to assess the effects of prophylactic doses of enoxaparin on antifactor Xa activity (anti-Xa) and rotational thromboelastometry (ROTEM) parameters in critically ill patients.Materials and methodsIn this prospective single-center cohort study, the effects of enoxaparin were assessed via anti-Xa monitoring. Standard laboratory coagulation and ROTEM parameters were also determined using the same blood samples.ResultsA total of 61 patients (42.6% women) were enrolled in this study, whose median age was 59.0 (interquartile range: 43.0–70.0) years. Based on anti-Xa, the effects of enoxaparin were normal in 35 subjects (57.4%); in 17 patients (27.9%), the anti-Xa troughs and/or peaks were higher than the prophylactic range; in 9 patients (14.7%), the anti-Xa peak was lower than the prophylactic range. There were differences among the anti-Xa groups with respect to some ROTEM parameters. No VTE was detected among the study subjects. In 3 subjects (4.9%), there were signs of bleeding, and these patients presented with longer thrombin times.ConclusionAnti-Xa values may be within the prophylactic range in slightly more than half of the critically ill patients receiving enoxaparin at prophylactic doses. The dosing of low-molecular-weight heparin (LMWH) in critically ill patients may require individualization based on anti-Xa. Further studies are therefore required to establish a universal anti-Xa prophylactic range for LMWH, the timing of anti-Xa determination, and management of LMWH dosing.